Constitution of the metabolic type of streptomycetes during the first hours of cultivation - Janecek, J; Tichý, P; Spízek, J; Vanĕk, Z (Folia microbiologica, 1997)
Using the examples of biosynthesis of streptomycin, bialaphos, actinorhodin, oligoketides and autoregulators during the first hours of streptomycete cultivation, it is stressed that the external environment in cooperation with the internal metabolic abilities of the cell determines the metabolic type that would develop during the life cycle of the producing streptomycetes. If we accept that a certain metabolic type (from the point of view of the production of secondary metabolites) was determined already during the first hours of cultivation of the microorganisms, we must also admit that the availability of primary metabolites in the so-called production phase of growth (stationary phase, idiophase, etc.) is to a certain extent determined by the very early stages of strain development.
Keywords: anthrachinony; časové faktory; Time Factors; streptomycin; Organophosphorus Compounds; organofosforové sloučeniny; Streptomyces; antibakteriální látky; Anthraquinones; Anti-Bacterial Agents; Gene Expression Regulation, Bacterial; regulace genové exprese u bakterií; Streptomycin